The Mental Well-Being of Frontline Physicians Working in Civil Wars Under Coronavirus Disease 2019 Pandemic Conditions - Elhadi, Muhammed; Msherghi, Ahmed; Elgzairi, Moutaz; Alhashimi, Ayiman; Bouhuwaish, Ahmad; Biala, Marwa; Abuelmeda, Seraj; Khel, Samer; Khaled, Ala; Alsoufi, Ahmed; Elhadi, Ahmed; BenGhatnsh, Ahmed (Frontiers in Psychiatry, 2021)
Background and Objective: Emergency medical physicians are regarded as essential frontline staff in combating the COVID-19 pandemic. These healthcare workers are faced with significant stressors in addition to the usual stress felt in their regular work. Therefore, this study aimed to examine the prevalence of anxiety, depression, and burnout among emergency physicians on the frontline of the COVID-19 pandemic. Method: Using a cross-sectional study methodology, we surveyed physicians active in April 2020 to study depression and anxiety (using HADS) and burnout (using the aMBI scale). Results: A total of 154 emergency physicians completed the survey. We found that about 65.6% of patients were experiencing anxiety (based on a HADS score ≥11), and 73.4% were displaying depressive symptoms. For burnout, three subscales indicated that 67.5% endured emotional exhaustion, and 48.1% experienced depersonalization (defined as a score of ≥10 on aMBI). A total of 21.4% of respondents perceived a sense of personal underachievement, defined as a score of <10 via aMBI. Conclusion: Physicians’ psychological status is crucial and plays a major role in their well-being, affecting their work satisfaction. Therefore, implementing strategies aimed at decreasing the impact of stressful events is crucial to alleviating the distress experienced by physicians on the frontline of the COVID-19 pandemic.